Systematic evaluation of stroke thrombectomy in clinical practice: The German Stroke Registry Endovascular Treatment. Issue 4 (June 2019) - Alegiani, Anna C; Dorn, Franziska; Herzberg, Moriz; Wollenweber, Frank A; Kellert, Lars; Siebert, Eberhard; Nolte, Christian H; von Rennenberg, Regina; Hattingen, Elke; Petzold, Gabor C; Bode, Felix J; Pfeilschifter, Waltraud; et al.
Background: Endovascular treatment has become standard of care for the treatment of acute ischemic stroke with large vessel occlusion. However, patients treated in clinical practice differ from the selected populations randomized in clinical trials. Aims: The German Stroke Registry Endovascular Treatment (GSR-ET) aims at a systematic evaluation of outcome, safety, and process parameters of endovascular stroke treatment in standard of care in Germany. Methods: The GSR-ET is an academic, independent, prospective, multicenter, observational registry study. Participating stroke centers from all over of Germany consecutively enroll patients transferred to the angiography suite with an intention to be treated with endovascular stroke treatment. Patients receive regular care. Data are collected as part of clinical routine. Baseline clinical and procedural information and clinical follow-up information after 90 days are recorded. Here, we present an analysis of baseline data of the first 1662 patients included in the GSR-ET. Results: The registry was established in June 2015. By 31 December 2017, 1662 patients were enrolled in 23 active sites. Mean age was 72 ± 13 years, 50% were female, and median National Institutes of Health Stroke Scale on admission was 15 (IQR 10–19), 88% had anterior circulation occlusion. Median ASPECT score was 8 (IQR 7–10) prior to intervention. Fifty-nine percent of patients received intravenous thrombolysis prior to thrombectomy. Mean "onset-to-groin" time was 224 ± 176 min. Conclusions: Baseline characteristics of stroke patients undergoing thrombectomy in clinical practice differ from those in the randomized trials. The GSR-ET will provide valuable insights into practices of endovascular treatment in routine care of acute ischemic stroke. (GSR-ET ClinicalTrials.gov Identifier: NCT03356392.)